Management of Environmental Protection Initiatives - Evidence from Sweden - Santosh, Kumar Mishra (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Environmental protection is one of the significant aspects of sustainable development (SD) of any country. Sweden is no exception, several environmental protection initiatives, including Environmental Governance Programme (EGP), have been undertaken by various stakeholders. The Swedish Government’s vision of SD envisages the principle that “all policy decisions must take account of the longer-term economic, social and environmental implications”. The terms environmental protection and SD have been used interchangeably in this paper. However, it is pertinent to note that it is a management aspect of environmental protection initiatives that require special attention on the part of programme managers. This empirical research aims to look into the management of selected environments and SD programmes undertaken in Sweden. Secondary data (mostly ‘qualitative’ in nature) have been used in the work, analysis methodology being ‘descriptive’, involving “desk-based research”. The paper concludes that the management of Swedish environmental protection initiatives adopts multi-disciplinary approaches.